A STATISTICAL STUDY ON FACTORS INFLUENCING ARTHRITISAMONG WORKING WOMEN (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
The purpose of the present study is to explore the factors that influence arthritis among working women. A sample of 200working women whose age more than 20 years is taken for the study. The data is collected through questionnaire methodusing 5-point Likert scale. The objective of this paper is also to find the most prominent type of arthritis for different agegroups, awareness, cause and medication for arthritis among working women. Exploratory Factor analysis is performedand five important factors that influence arthritis is extracted. The five factors are named as Personal stress, calciumdeficiency, obese, hereditary and age.